Knowledge and Attitude of Physicians Toward Management of Type 2 Diabetes Mellitus at Benghazi Medical Center - Hassan, Malak Nasser; Buzaid, Najat Omer (Libyan International Medical University Journal, 2025)
Type 2 diabetes mellitus (T2DM) is a major public health problem with an increased prevalence; many physicians come into contact with patients with T2DM, thus their knowledge and management attitudes play a vital role in patient care and proper management.To evaluate the knowledge and attitude of physicians working at Benghazi Medical Center (BMC), toward T2DM and its management, and to identify factors that affect their knowledge and attitude.A facility-based cross-sectional analysis was conducted at BMC between June 2023 and April 2024, enrolling 140 practicing physicians (excluding endocrinology specialists). Participants completed an adapted 28-item questionnaire evaluating both cognitive knowledge (diagnostic criteria, therapeutic targets) and clinical attitudes (management behaviors). Scoring thresholds classified knowledge as poor (< 50%), moderate (50–75%), or good (> 75%), while attitudes were binary-classified (poor < 70% vs. good ≥ 70%). Statistical testing was performed using SPSS 24, employing chi-square tests for proportions and multivariable regression to identify predictors, with α = 0.05 defining significance. Continuous measures appear as mean ± standard deviation and categorical data as counts/percentages.Among 140 physicians (86.4% female, mean age 36.1 ± 5.39 years), knowledge levels were moderate (52.1%) to good (15%), with significant gaps in lipid targets and hypoglycemia recognition. Notably, 56.4% demonstrated poor management attitudes. Work experience > 10 years predicted superior knowledge (p < 0.02), while specialists and residents showed better attitudes than consultants (p < 0.01). Correct diagnosis thresholds were known (fasting plasma glucose: 88.6%, hemoglobin A1c: 83.6%), but treatment indications showed variability (insulin: 66.4%). These findings highlight critical knowledge-practice gaps in T2DM management.The majority of participants had a moderate to good level of knowledge about T2DM. A higher percentage had poor attitudes toward T2DM management, while their attitudes toward using antidiabetic medications were average. These findings call for institutional reforms in diabetes training, emphasizing guideline adoption and attitudinal improvement, particularly for senior clinicians.
Keywords: knowledge; attitude; physicians; T2DM; management; Benghazi